Clinical and Imaging Predictors of Disease Progression in Type B Aortic Intramural Hematomas and Penetrating Aortic Ulcers: A Systematic Review - Elda Chiara Colacchio; Francesco Squizzato; Michele Piazza; Mirko Menegolo; Franco Grego; Michele Antonello (Diagnostics, 2022)
Background: This work aims to review recent literature on penetrating aortic ulcers (PAUs) and intramural hematomas (IMHs), in order to identify clinical and imaging factors connected to aortic-related adverse events (AAE). Methods: We performed a systematic review according to the Preferred Reporting Items for Systematic review and Metanalyses (PRISMA) guidelines. An electronic search was conducted on Medline and Embase databases. We included articles reporting on PAUs and/or IMHs localized in the descending thoracic and/or abdominal aorta and analyzing clinical and/or radiological markers of AAE. Results: Of 964 records identified through database searching, 17 were incorporated in the present review, including 193 and 1298 patients with type B PAUs and IMHs, respectively. The 30-days aortic-related mortality (ARM) was 4.3% and 3.9% for PAUs and IMHs. A total of 21% of patients with IMHs underwent intervention during the follow-up period, and 32% experienced an AAE. PAU markers of AAE were minimum depth (ranging from 9.5 to 15 mm) and diameter (≥12.5 mm). Maximum aortic diameter (MAD) cut-off values ranging from 38 to 44.75 mm were related to AAE for IMHs, together with ulcer-like projection (ULP) of the aortic wall. Conclusions: Despite data heterogeneity in the literature, this PAU- and IMH-focused review has highlighted the imaging and clinical markers of disease progression, thus identifying patients that could benefit from an early intervention in order to reduce the AAE rate.